The willow (Salix sp.) toothpicks from the Cistercian Monastery of Lorvão (Penacova, Portugal) - Carvalho, Luis; Fernandes, Francisca Maria; Nozes, Paula; Figueira, Ana Paula; Albuquerque, Sara; Silva, Paula; Nunes, Maria de Fátima (Ethnobotany Research and Applications, 2024)
In Portugal, the tradition of handmade white willow (Salix alba L.) toothpicks began in the Cistercian Monastery of Lorvão (Penacova), in an uncertain date during the 17th century. After the suppression of all monastic orders (1834), people from Lorvão continued this craft and, later, this parish became the main Portuguese center of the toothpick industry, an activity that still flourishes today. Handmade toothpicks, following ancient methods, are now made as a cultural symbol of the Penacova region. Keywords willow wood, toothpicks, monastery traditions.